High-Voltage High-Capacity Active Filter Technology for High Voltage DC Converter Station - WANG Ling, MA Weimin, JI Yiming, LI Ming, WU Fangjie, XU Ying, DU Xiaolei, ZHANG Xiujuan (Dianli jianshe)
[Objective] High-voltage direct current transmission technology is a core technical method for optimizing resource allocation in China. Traditional high-voltage direct-current transmission technology has many drawbacks， such as a large footprint and easily changing AC system resonance. Development of active filter technology for high-voltage converter stations is crucial in high-voltage direct-current transmission projects for adapting to the changes in the grid structure brought about by large-scale new energy access. This technology would solve the inherent defects of traditional passive filters and enable adaptation to the fluctuations in the current AC power grid. [Methods] This study was conducted from the multiple aspects of topology structure， working principle， scheme design， and engineering applications. A coordinated control method of multiple active filters is proposed for high-voltage and large-capacity active filters along with a steady-state parameter design and control strategy scheme， and further verified through various simulation methods， fully demonstrating the harmonic filtering and reactive power compensation capabilities of high-voltage and large-capacity active filters and their ability to support reactive power in the system. [Results] The results indicate that high-voltage high-capacity active filters can enhance the adaptability of traditional DC to weak AC systems， improve harmonic characteristics， optimize the converter station layout， and effectively support the strength of AC systems. [Conclusions] The research and application of high-voltage and high-capacity active filters provide the necessary guidance for the design of DC transmission engineering systems in the context of future development of new power systems.